Comparison of NIRS exercise intensity thresholds with maximal lactate steady state, critical power and rowing performance - Possamai, L. T.; Borszcz, F. K.; Aguiar, R. A.; Lucas, R. D.; Turnes, T. (Biology of Sport, 2024)
This study aimed to compare the intensity of deoxygenated haemoglobin concentration ([HHb]) and tissue saturation index (TSI) breakpoints ([HHb]-BP and TSI-BP) with maximal lactate steady state (MLSS)and critical power (CP), and to describe their association with2000-m rowing ergometer performance. Fourteen male rowers performed on a rowing ergometer: I) a discontinuous incremental test with 3-min stages (INC3); II) a continuous incremental test with 1-min stages (INC1); III) constant workload tests to determine MLSS; and IV) performance tests of 500 m, 1000 m, 2000 m and 6000 m to determine CP. CP (257±39 W; 3.79±4.1 L·min-1) was higher than [HHb]-BP3 (205±26 W; 3.48±2.9 L·min-1), [HHb]-BP1 (207±27 W; 3.27±3.2 L·min-1), and TSI-BP3 (218±31 W; 3.51±3.0 L·min-1), but not higher than TSI-BP1 (222±34 W; 3.43±3.2 L·min-1). MLSS (187±26 W; 3.33±3.2 L·min-1) was lower than TSI-BP3 and TSI-BP1 for power output, but not different in any comparison for VO2. The limits of agreement for power output and VO2 suggest poor agreement among these thresholds. The low level of agreement compromises the use of [HHb]-BP and TSI-BP for estimating MLSS and CP; therefore, these thresholds should not be considered interchangeable.